Mature Working Student Parents Navigating Multiple Roles: A Qualitative Analysis - Cláudia Andrade; Joana Lobo Fernandes; Leandro S. Almeida (MDPI AG, 2024)
Managing multiple roles is considered a major challenge that mature working student parents face when they embrace the educational pursuit of enrolling in higher education. Limited research exists on mature working student parents that identify the strategies that concur for a successful journey through their educational paths. The aim of this study is to explore the experiences of mature working student parents balancing studies, work, and family. We conducted 11 semi-structured interviews with mature students enrolled in first- and second-cycle degrees in a higher education institution in Portugal. Thematic analysis was used, and findings demonstrated that working student parents develop diverse strategies to combine work, family, and studies and these strategies are shaped by the needs they have in each role and interconnect with the activation of social support. Recommendations for researchers and institutions to support the educational pursuits of mature working student parents to best suit their needs are discussed.